Evaluasi Awal Politik Pemerintahan Baru dan Harapan Rakyat - Bambang Cipto (Unisia, 2005)
Susilo Bambang Yudoyono constitutes the first President of Indonesia who has been elected directly by Indonesian people. The election of president directly declares that although democracy in Indonesia still limited, there is significant changing in Indonesian political life in particular if this situation compares to before beginning reformation in Indonesia. This article tries to explain the relation management between President and Legislators, this part is so important because for the first time a president becomes the leader of state without strong party supporting. Secondly, the writer describes the crucial problem of the state regarding law enforcement because it is central part of government public relations. The third states welfare of people, the successful orthe failure of welfare politic denotes a heavy task for president in new democracy nations.